Devaluing memories of reward: a case for dopamine - Benjamin R. Fry; Nicolette Russell; Victoria Fex; Bing Mo; Nathan Pence; Joseph A. Beatty; Fredric P. Manfredsson; Brandon A. Toth; Christian R. Burgess; Samuel Gershman; Alexander W. Johnson (Communications Biology)
Abstract Midbrain dopamine cells encode differences in predictive and expected value to support learning through reward prediction error. Recent findings have questioned whether reward prediction error can fully account for dopamine function and suggest a more complex role for dopamine in encoding detailed features of the reward environment. In this series of studies, we describe a novel role for dopamine in devaluing sensory features of reward. Mesencephalic dopamine cells activated during a mediated devaluation phase were later chemogenetically reactivated. This retrieval of the devalued reward memory elicited a reduction in the hedonic evaluation of sucrose reward. Through optogenetic and chemogenetic manipulations, we confirm dopamine cells are both sufficient and necessary for mediated devaluation, and retrieval of these memories reflected dopamine release in the nucleus accumbens. Consistent with our computational modeling data, our findings indicate a critical role for dopamine in encoding predictive representations of the sensory features of reinforcement. Overall, we elucidate a novel role for dopamine function in mediated devaluation and illuminate a more elaborate framework through which dopamine encodes reinforcement signals.